Status and use of Pterocarpus lucens Lepr. in Sahelian ecosystems - Cisse, M.I.; Wilson, R.T. (Australian Academy of Science, 1985)
Describes the status and use of pterocarpus lucens Lepr. in the northern African semi-arid tropical zones. Outlines the botanical description and phenology. Discusses formation containing p. lucens in central Mali and its economic roles which includes forage supply, fuel wood & traditional medicine.